SMART TECHNOLOGIES IN THE DESIGN OF ELECTRIC LIGHTING SYSTEMS - Третякова , Лариса; Мітюк, Людмила; Качинська, Наталія (Art and Design, 2024)
Objective: To analyse traditional elements of electrical engineering systems of artificial lighting of premises of various purposes, to substantiate energy and economic feasibility of new approaches to design and to propose algorithms for the design of lighting system based on the introduction of "smart" technologies, energy-saving electrical devices and electrical networks to comply with regulatory requirements. Methodology. Methods of analysis and comparison of advantages and disadvantages of LED lighting sources were used. The basic provisions of lighting engineering, optical and lighting characteristics of light sources and radiation in the material medium and methods of lighting calculations were used in the analysis. Results. The article formulates the basic principles of designing or modernizing a modern indoor artificial lighting system based on the Smart home concept, which provides for automatic control of energy-saving engineering lighting systems inside and outside the premises of any purpose. The "smart" technologies in indoor lighting systems are analysed, the introduction of which allows to solve the set tasks − to ensure compatibility of regulatory requirements, lighting characteristics, electrical parameters, financial and ergonomic indicators. According to the results of comparison of light electrical and financial characteristics of lighting sources, the conclusion about the feasibility of using LED light sources was made. Scientific novelty. An algorithm for designing a lighting system based on the introduction of "smart" technologies, energy-saving electrical devices and electrical networks to meet the regulatory requirements of power quality and illuminance level has been developed. Practical significance. It is suggested that when choosing a project or modernization of the lighting system to focus on the efficiency factor, which combines the main lighting and financial indicators.